2014
DOI: 10.1016/j.brat.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Extinction of cue-evoked drug-seeking relies on degrading hierarchical instrumental expectancies

Abstract: There has long been need for a behavioural intervention that attenuates cue-evoked drug-seeking, but the optimal method remains obscure. To address this, we report three approaches to extinguish cue-evoked drug-seeking measured in a Pavlovian to instrumental transfer design, in non-treatment seeking adult smokers and alcohol drinkers. The results showed that the ability of a drug stimulus to transfer control over a separately trained drug-seeking response was not affected by the stimulus undergoing Pavlovian e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
86
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(101 citation statements)
references
References 78 publications
14
86
1
Order By: Relevance
“…Using this approach, animal PIT studies have shown that a CS for food or sucrose continues to produce selective facilitation of an instrumental response for the same reward despite intervening Pavlovian extinction (Delamater, 1996;Holmes et al, 2010). A similar result has been reported in the only two studies we know of that have tested the effect of Pavlovian extinction on PIT in humans (Hogarth et al, 2014;Rosas, Paredes-Olay, García-Gutiérrez, Espinosa, & Abad, 2010). Together, these results suggest that the ability of a reward cue to promote reward-directed behavior may survive simple extinction.…”
supporting
confidence: 53%
“…Using this approach, animal PIT studies have shown that a CS for food or sucrose continues to produce selective facilitation of an instrumental response for the same reward despite intervening Pavlovian extinction (Delamater, 1996;Holmes et al, 2010). A similar result has been reported in the only two studies we know of that have tested the effect of Pavlovian extinction on PIT in humans (Hogarth et al, 2014;Rosas, Paredes-Olay, García-Gutiérrez, Espinosa, & Abad, 2010). Together, these results suggest that the ability of a reward cue to promote reward-directed behavior may survive simple extinction.…”
supporting
confidence: 53%
“…These two forms of knowledge are then synthesized in a cognitive inference. The experience of an adverse state generates an expectation of the greater reinforcement value of smoking which is combined with goal‐directed instrumental knowledge of the response sequence required to produce the desired smoking outcome given the specific external context . The incentive learning account is unique among the categories of negative reinforcement theory in predicting that adverse internal states prime smoking behavior via a conjunction of subjective desire to smoke and instrumental knowledge of the responses required to produce that outcome in the current context.…”
Section: Psychological Mechanisms Promoting Smoking Maintenance and Rmentioning
confidence: 99%
“…This systematic review provides an update of the current state of evidence on the topic of co‐occurring smoking and depression and proposes a novel application of incentive learning theory to conceptualize smoking persistence among depressed smokers. As detailed below, the incentive learning account has gained considerable empirical support in the study of drug dependence , and offers a unique lens through which to view the clinical problem of smoking and depression. In particular, incentive learning theory proposes that specific states drive goal‐directed selection of smoking behavior over alternate choices for depressed smokers.…”
Section: Introductionmentioning
confidence: 99%
“…Degrading expectations has been shown to be an effective method to extinguish cue-induced drug seeking in addicts (Hogarth et al, 2014). Remarkably, significant activation of the cerebellum was observed when subjects were faced with a cocaine-related interview that included recall of previous drug experiences (Wang et al, 1999).…”
Section: The Cerebellum's Role: Craving or Prediction?mentioning
confidence: 99%